Inexact two-point Newton-like methods - Magreñán, Á. Alberto; Argyros, Ioannis K (Elsevier, 2024)
In this chapter the applicability of inexact two-point Newton-like method for solving nonlinear equations is extended. Moreover, we present some numerical examples validating the theoretical results.
Es un capítulo del libro: Magreñán, A. A., & Argyros, I.K. (2018). A Contemporary Study of Iterative Methods Convergence, Dynamics and Applications. Elsevier
Keywords: Newton-like method; iterative methods; nonlinear equations; WOS(2)